El «problema del indio» y la elección de Castillo: el desafío de re-imaginar un nuevo Perú - Valderrama Aguayo, Ivan Jesús (2022)
The objective of this work is to analyze from a critical perspective the current political situation that on June 6materialized in the election, as the new President of the Republic, of Pedro Castillo in Peru. Said analysis, materialized from the categories of thought proposed by authors such as Mariátegui and González Prada, aims to guide the configuration of imagined-future scenarios that seek to vindicate the importance of the 'Indian' as a leading subject of the socio-historical development of Peru, the which he considers as one of his main recent milestones the election of Castillo as the first national authority. Finally, practical mechanisms are proposed that contribute to configuring these scenarios as a mechanism through which to combat the historical invisibility of 'the Indians', a direct result of domination, in the spheres of power, knowledge and being.